Tzvetan Todorov. La littérature en péril. Flammarion, Café Voltaire. 2007. - Alonso-Rey, María Dolores (Estudios Humanísticos. Filología, 2008)
Tzvetan Todorov. La littérature en péril. Flammarion, Café Voltaire. 2007.